INDUKSI MUTASI KULTUR IN VITRO Amorphophallus muelleri Blume DENGAN IRRADIASI GAMMA - Poerba, Yuyu S; IMELDA, MARIA; WULANSARI, AIDA; MARTANTI, DIYAH (Jurnal Teknologi Lingkungan, 2009)
Amorphophallus muelleri Blume (Araceae) is valued for its glucoman content for use infood industry (heathy diet food), paper industry, pharmacy and cosmetics. The cultivationof A. muelleri is hampered by limited genetic quality of seed. The species is triploid(2n=3x=39), the seed is developed apomictically, and pollen production is low. Thespecies is only propagated vegetatively. This may explain that the species is difficultto breed conventionally and genetic variability in the existing landraces cultivars israther limited. Conservation of this species, therefore, is important for availability of thespecies in the future use of this plant. The objective of present research is to increasegenetic variation by induce mutation using gamma-rays irradiation of shoot culturesof A. muelleri and to identify DNA polymorphism induced by gamma irradiation usingrandom amplified polymorphic DNA (RAPD), so the mutants produced can be used forbreeding purposes and for conservation program. Results of the experiment showedthat gamma irradiation less than 5 gray was effective to induce mutation of A. muelleri.Four RAPD primers generated 35 scorable bands with 100% polymorphic bands. Sizeof the bands varied from 350bp to 2.0kbp. Clustering analysis was performed based onRAPD profiles using the UPGMA method. The range of genetic distance among individualgenotypes was from from 0.00 to 0.72, while genetic variance of the population was0.21 + 0.13. The eighteen genotypes were proof to be mutants. The mutants producedin this experiment could be used as new germplasms for breeding purposes as well asfor use in conservation strategy